The greater goal : connecting purpose and performance - Jennings, Ken (Kenneth R.); Hyde, Heather (San Francisco, CA : Berrett-Koehler Publishers, 2012)
'A purpose-driven organization, one aligned around a goal that goes beyond the bottom line to touch on deeper human aspirations, is one of the most powerful forces on earth. But simply having a greater goal, important as that is, isn't enough. Leaders also have to know how to make that goal the foundation of their overall strategy, and how to execute that strategy while staying true to the larger purpose. Using a business fable format, Ken Jennings and Heather Hyde lay out a five point plan they call'The Star Model' that guides leaders through the process of creating profoundly motivating purpose, achieving enthusiastic buy-in from the organization, and aligning an entire organization, at all levels, to this greater goal. Incorporating their research and many years of experience in strategic advisory services, executive development, and culture change, Jennings and Hyde tell the story of Alex Beckley, the new president of a medical products company who receives a dramatic wake-up call that demands he live and lead differently. The Star Model transforms not only his work life, but his personal life as well.'--
Keywords: Leadership; Goal (Psychology).; Strategy; Motivation (Psychology).; Organizational effectiveness